The effect of general anaesthesia on gastric myoelectric activity in experimental pigs - Tachecí, Ilja; Květina, Jaroslav; Kuneš, Martin; Pavlík, Michal; Kopáčová, Marcela; Černý, Vladimír; Rejchrt, Stanislav; Edakkanambeth Varayil, Jithinraj; Bureš, Jan (BMC gastroenterology, 2013)
BACKGROUND: Surface electrogastrography (EGG) is a non-invasive method for clinical assessment of gastric myoelectrical activity. Different forms of general anaesthesia might have various effects on porcine EGG. The aim of this study was to evaluate the impact of different anaesthetic agents on EGG in experimental pigs. METHODS: Four 15-minute EGG intervals were recorded and analysed. A baseline EGG recording was started 20 minutes after intramuscular injection of ketamine and azaperone (periods A and B). Four different regimens of general anaesthesia followed immediately after the baseline EGG (5 pigs in each experimental group): thiopental, isoflurane, nitrous oxide and isoflurane plus nitrous oxide. EGG recordings followed for the next 30 minutes under general anaesthesia (periods C and D). The dominant frequencies of slow waves were compared between the baseline intervals A and B and periods C and D under general anaesthesia. RESULTS: The mean dominant frequency was within the normal range (2.3 - 3.5 cycles per minute) in all animals in all regimens. Thiopental general anaesthesia did not influence any change of the dominant frequency of slow waves. Nitrous oxide general anaesthesia increased the dominant frequency of slow waves in a statistically significant manner (baseline: 2.93 ± 0.53 and 3.01 ± 0.53; under general anaesthesia: 3.25 ± 0.34 and 3.29 ± 0.38 cycles per minute; p < 0.001, p = 0.003, p < 0.001, p < 0.001). Nitrous oxide together with isoflurane induced a statistically significant decrease of dominant frequency in the last 15-minute interval (2.66 ± 0.55 cycles per minute) compared to the baseline recording (2.81 ± 0.49; p = 0.030). CONCLUSIONS: All changes of porcine gastric myoelectric activity assessed by the dominant frequency of slow waves during EGG remained within the normal range although some of them achieved statistical significance. Thus all tested agents used for general anaesthesia can be recommended in preclinical studies with porcine models focused on gastric myoelectric activity without any risk of compromising the results. Thiopental seems to be the most suitable as it did not cause any changes at all.
Keywords: Animals; Female; Anesthetics, General; thiopental; ženské pohlaví; migrující myoelektrický komplex; prasata; Models, Animal; Isoflurane; isofluran; Nitrous Oxide; žaludek; Swine; Thiopental; anestetika celková; zvířata; oxid dusný; Myoelectric Complex, Migrating; Stomach; modely u zvířat